2012
DOI: 10.3390/ph5060629
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Bifidobacteria on the Development of Gut Bifidobacteria in Infants

Abstract: Intestinal microbiota plays an important role in human health by influencing metabolic activities that result in the creation of energy and absorbable nutrients, a barrier to the colonization of pathogens, and stimulation of the immune system. The development of fecal microbiota in neonates is crucial because those bacteria are the first to colonize the sterile intestine of the neonates and, thus, have a significant effect on the host. Initial colonization is also relevant to the final composition of the perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 56 publications
2
31
0
2
Order By: Relevance
“…Bifidobacteria are important colonizers of an infant's gut during lactation, and evidence is accumulating that the strains found in the infant are vertically obtained from the mother (Mikami et al . ). The original source of these commensal bacteria is probably the mother's gut microbiome.…”
Section: How Mothers Pass Their Bacteria On To Their Babiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Bifidobacteria are important colonizers of an infant's gut during lactation, and evidence is accumulating that the strains found in the infant are vertically obtained from the mother (Mikami et al . ). The original source of these commensal bacteria is probably the mother's gut microbiome.…”
Section: How Mothers Pass Their Bacteria On To Their Babiesmentioning
confidence: 97%
“…It has been known for some time that human milk is not sterile either; notably, it contains bifidobacteria and lactobacilli (Mart ın et al 2003(Mart ın et al , 2009. Bifidobacteria are important colonizers of an infant's gut during lactation, and evidence is accumulating that the strains found in the infant are vertically obtained from the mother (Mikami et al 2012). The original source of these commensal bacteria is probably the mother's gut microbiome.…”
Section: How Mothers Pass Their Bacteria On To Their Babiesmentioning
confidence: 99%
“…The DOHaD concept suggests that the maternal microbiome shapes the microbiome composition in the offspring . The maternal vaginal and gut microbiota typically form the first microbial inoculum at birth . Studies have shown that vaginally born infants acquire Bifidobacterium and Bacteroides from their mothers .…”
Section: Resultsmentioning
confidence: 99%
“…The maternal vaginal and gut microbiota typically form the first microbial inoculum at birth . Studies have shown that vaginally born infants acquire Bifidobacterium and Bacteroides from their mothers . These early colonisers have roles in human milk oligosaccharides (HMOS) metabolism and resistance as well as in the host immune and metabolic programming …”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, new strains (that display different genomic content and potential carbohydrate metabolism capabilities) can be acquired, possibly in response to the changing diet. Initial vertical acquisition of Bifidobacterium from mother to newborn babies has been well documented ( 48, 49, 73 ); however, details of strain transmission events in later life are currently unclear. Work of Odamaki et al ( 42 ) identified person-to-person horizontal transmission of a particular B. longum strain between members of the same family, and suggested direct transfer, common dietary sources or environmental reservoirs, such as family homes ( 74 ), as potential vehicles and routes for strain transmission.…”
Section: Discussionmentioning
confidence: 99%